Extracción del aceite esencial de matico (Piper aduncum), mediante el método de arrastre de vapor. - Bedón Ponluisa, Karen Andrea (2022)
The present investigation was developed with the objective to extract e ssential matico (Piper aduncum) oil, by steam drag method, for this purpose Lanphan Ltd. China laboratory equipment of Agricultural Sciences and Natural Resources Faculty (CAREN) of Technical University of Cotopaxi was used, where the best experimental extraction conditions were determined at relation to time and mass/solvent to obtain the highest yield. For statistical treatment, program Desing Expert 8.0.6 was used with an optimal response surface design V, 17 runs were generated at three different times (60, 90 and 120 min) and mass/solvent (1:3; 1:4 and 1:5 kg/L) at a constant temperature of 100 °C. The best result was obtained at run number 2 (120 min time, mass/solvent 1:5 kg/L) with a yield of 0,8843 %. In addition, chemical composition of optimized essential oil was analyzed by gas chromatography coupled to a mass detector, identifying 17 volatile compounds, those found in greater proportion were D-germacrene (32,37 %) and 1,14-Epoxyherberthene (24,73 %), at the same time antioxidant activity analysis was performed by the FRAP and ABTS method giving as a result 180,24 µmol Fe2+/g and 90,23 µmol ET/g. Evaluating antimicrobial activity by minimum inhibitory concentration method of matico (Piper aduncum), essential oil an efficacy of 1mg/L was found for Salmonella enterica and Staphylococcus aureus ATCC 25923 and 0,5 mg/L for Escherichia coli ATCC 25922 and Pseudomonas aeruginosa ATTC 39327.